1. $9\times 8 = 72$
$9+8=17$
$p^2+9p+8p+72$
$p(p+9)+8(p+9)$
$(p+9)(p+8)$
2. $9\times -8=-72$
$9+-8=1$
$x^2+9x-8x-72$
$x(x+9)-8(x+9)$
$(x+9)(x-8)$
3. $-8\times -1 = 8$
$-8+-1=-9$
$n^2-n-8n+8$
$n(n-1)-8(n-1)$
$(n-1)(n-8)$
4. $6\times -5 = -30$
$6+-5=1$
$x^2+6x-5x-30$
$x(x+6)-5(x+6)$
$(x+6)(x-5)$
5. $-10\times 1 = -10$
$-10+1=-9$
$x^2-10x+x-10$
$x(x-10)+1(x-10)$
$(x-10)(x+1)$
6. $8\times 5 = 40$
$8+5=13$
$x^2+8x+5x+40$
$x(x+8)+5(x+8)$
$(x+8)(x+5)$
7. $4\times 8 =32$
$4+8=12$
$b^2+4b+8b+32$
$b(b+4)+8(b+4)$
$(b+4)(b+8)$
8. $-7\times -10=70$
$-7+-10=-17$
$b^2-7b-10b+70$
$b(b-7)-10(b-7)$
$(b-7)(b-10)$
9. $-3\times -5=15$
$-3+-5=-8$
$u^2-3uv-5uv+15v^2$
$u(u-3v)-5v(u-3v)$
$(u-3v)(u-5v)$
10. $-8\times 5 =-40$
$-8+5=-3$
$m^2-8mn+5mn-40n^2$
$m(m-8n)+5n(m-8n)$
$(m-8n)(m+5n)$
11. $4\times -2=-8$
$4+-2=2$
$m^2+4mn-2mn-8n^2$
$m(m+4n)-2n(m+4n)$
$(m+4n)(m-2n)$
12. $8\times 2=16$
$8+2=10$
$x^2+8xy+2xy+16y^2$
$x(x+8y)+2y(x+8y)$
$(x+8y)(x+2y)$
13. $-9\times -2=18$
$-9+-2=-11$
$x^2-9xy-2xy+18y^2$
$x(x-9y)-2y(x-9y)$
$(x-9y)(x-2y)$
14. $-2\times -7=14$
$-2+-7=-9$
$u^2-2uv-7uv+14v^2$
$u(u-2v)-7v(u-2v)$
$(u-2v)(u-7v)$
15. $4\times -3=-12$
$4+-3=1$
$x^2+4xy-3xy-12y^2$
$x(x+4y)-3y(x+4y)$
$(x+4y)(x-3y)$
16. $5\times 9=45$
$5+9=14$
$x^2+5xy+9xy+45y^2$
$x(x+5y)+9y(x+5y)$
$(x+5y)(x+9y)$